Efecto de los juegos recreativos para la fuerza en estudiantes de 10mo A, de la Unidad Educativa Lauro Damerval Ayora, Loja, 2023-2024. - Tillaguango Jiménez, Byron Gustavo (2024)
The present work of curricular integration was carried out with the purpose of examining the effect of recreational games on the development of strength in 10th grade students of General Basic Education, parallel A, in the Unidad Educativa Lauro Damerval Ayora of the city of Loja, during the period 2023-2024. A mixed approach was implemented, combining descriptive and correlational elements, and a quasi-experimental design was chosen. For data collection, research instruments such as the survey, aimed at assessing the students' knowledge of recreational games, and physical assessment tests were used, with the objective of diagnosing the state of strength both before and after the intervention. These instruments were applied to a sample of 26 participants. The results obtained revealed a significant increase in the students' strength in the post-tests. In the case of the ball throw, 42% of results were obtained in a good condition, while, in the vertical jump test, 46% of the population showed a good condition. Likewise, the vertical jump test showed 4% in an excellent level. These data indicate a positive change compared to the results of the initial pre-test. It is important to note that these findings were associated with the implementation of a pedagogical proposal composed of 18 program-related plans. Finally, it was observed that, prior to the implementation of the pedagogical proposal, some students presented low levels of strength in relation to their age and gender. These results underline the effectiveness of recreational games as a teaching strategy focused on the improvement of conditional capacities, especially strength. Key words: recreational games, strength, teaching strategy and physical assessment.